Nationalism : Theories and cases - "Harris, Erika" (Edinburgh, 2009)
This highly original contribution to studies of nationalism focuses on its ideological foundations, tracing its historical beginnings and charting its varied manifestations in world politics today. Its broad theoretical and empirical inquiry explores the dynamics of nationalism and its theories and also considers the role of 'the nation' in political processes taking place beyond states. In addition to a wide-ranging review of traditional approaches to nationalism, this book is unique in its broad geographic and historical scope and in the appraisal of these approaches in contemporary international politics, including developments such as the increased role of non-state actors, regional integration, trans-national movements and diasporas. A key element of the book is its case studies which range from the rise of national movements within the old Empires to contemporary ethnic conflicts, and which allow for a clearer understanding of the politics of nationalism, how its theories can be applied and which urge some searching questions about 'new' forms of ethno-national mobilization. Key Features *Only book to cover both historical and contemporary theories of nationalism *Reviews classical theories of nationalism *Shows nationalism to be integral to all political changes and demonstrates its relevance to democracy and globalisation *Uses examples and case studies to demonstrate application of theories of nationalism in world politics *Links classical and 'new' nationalism - continuities and discontinuities between the 'old' and current understandings of nationalism are highlighted
Keywords: Nationalism